2021
DOI: 10.1108/ijge-07-2021-0115
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding, gender and the promise of financial democracy: a systematic review

Abstract: PurposeThe purpose of this study is to review the literature at the intersection of crowdfunding and gender, while examining the extent to which crowdfunding has enhanced female financial inclusion and participation.Design/methodology/approachA systematic literature review was conducted across 47 studies from 2011 to April 2021.FindingsMost studies suggest that the likelihood of success or failure of female-led campaigns depends on external factors associated with opportunities. The study points to a general t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 90 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…Research at the intersection of crowdfunding backing behavior and gender has primarily focused on the underrepresentation of female entrepreneurs on the demand side (Elitzur & Solodoha, 2021; Johnson et al, 2018), with limited attention given to women as funding providers on the supply side. The few studies that addressed gender differences in crowdfunding backer behavior have generally observed similar patterns to those in traditional entrepreneurial finance (Gafni et al, 2020; Serwaah, 2022).…”
Section: Literature Review: Gender and Funding Decisionsmentioning
confidence: 82%
See 1 more Smart Citation
“…Research at the intersection of crowdfunding backing behavior and gender has primarily focused on the underrepresentation of female entrepreneurs on the demand side (Elitzur & Solodoha, 2021; Johnson et al, 2018), with limited attention given to women as funding providers on the supply side. The few studies that addressed gender differences in crowdfunding backer behavior have generally observed similar patterns to those in traditional entrepreneurial finance (Gafni et al, 2020; Serwaah, 2022).…”
Section: Literature Review: Gender and Funding Decisionsmentioning
confidence: 82%
“…Despite this, gender differences in venture funding seem to persist also in the context of crowdfunding. A recent literature review by Serwaah (2022) argues that gender differences may manifest with respect to motivation, ability, and opportunity to financially back crowdfunding campaigns. Hence, when examining actual compositions of crowdfunding backer groups, recent global statistics from 2020 show that women only represent 30% of equity crowdfunding investors, 18% of real estate crowdfunding investors, 24% of business crowdlenders, 23% of property crowdlenders, and 33% of reward crowdfunding backers (Ziegler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the impact of Fintech sector development on SME businesses, the range of Fintech services is expanding to include not only mobile payments but crowd financing (Kim & De Moor, 2017;Serwaah, 2021), artificial intelligence solutions for more accurate SME credit assessments (Bughin et al, 2017(Bughin et al, , 2019Rybakovas & Žigienė, 2021;Taylor, 2018;Westermann, 2018;Zhang et al, 2018;Žigienė et al, 2019), the impact of platform economies (Langley & Leyshon, 2021) on financing, and more. The application of individual technologies helps SMEs to overcome the barrier of access to finance for business development, thus the potential of increasing business financial inclusion.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
“…Barasinska and Schäfer (2014) stated that "female discrimination seems to be eased by the 'wisdom of the lending crowd,'" while Bapna and Ganco's (2021) research confirms that the gender gaps observed in traditional equity funding do not apply to equity crowdfunding. Serwaah (2022) points to a general trend where female participation has not achieved its full potential; it is more significant than in other channels while enjoying higher chances of success for female fundraisers. Figueroa-Armijos and Berns (2022) also advocated that preliminary evidence suggests crowdfunding increasingly lessens the gender bias between crowdfunders and entrepreneurs, particularly in a prosocial context.…”
Section: Introductionmentioning
confidence: 99%